The Role of School Administrators in the Management of the Intensive Islamic Curriculum under Pattani Primary Educational Servic Area Office 2 - Dohloh, Suraida (Al-HIKMAH Journal, 2022)
Abstract The purposes of this research were to study (1.) the level of the role of school administrators (2.) the level of management of the intensive islamic curriculum (3.) to compare the role of school administrators by variables of gender, old and size of schools. (4.) to compare the management of the intensive islamic curriculum by variables of gender, old and size of schools. (5) the relationship between the role of school administrators and management of the intensive islamic curriculum and (6) to analyze suggestions about the role of school administrators and management of the intensive islamic curriculum under Pattani Primary Educational Servic Area Office 2. The sample used in the research was a group of 272 teachers under Pattani Primary Educational Servic Area Office 2 selected by using the Taro Yamane formula.The tool used were 5 rating scale by Likert for 4 parts questionnaire which consisted of 4 part of 4 parts of questionnaire. The statistics used for data analysis were : percentage, mean, standard deviation, t-Test, F-Test. When there was difference, it would be testd by Scheffe’s Method and Pearson’s Correlation Coefficient. The results of the research were as follows : The role of school administrators under Pattani Primary Educational Servic Area Office 2, as a whole and in each aspect was at a high level. The management of the intensive islamic curriculum under Pattani Primary Educational Servic Area Office 2, as a whole and in each aspect was at a high level. The comparison of the role of school administrators under Pattani Primary Educational Servic Area Office 2 classified by variables of gender, old and size of schools. In overall were no different accept position working experience as a whole and in each aspect were statistically significant differences at .05. The comparison of the management of the intensive islamic curriculum under Pattani Primary Educational Servic Area Office 2 classified by variables of gender, old and size of schools. In overall were no different accept position working experience as a whole and in each aspect were statistically significant differences at .05. The relationship between the role of school administrators and management of the intensive islamic curriculum. In overall were statistically significant differences at .01 which a positive relationship in a high level. The compilation suggestions about the role of school administrators and management of the intensive islamic curriculum found that administrators should facilitate the management of the intensive islamic curriculum, focus on curriculum, to advice every thing, to support planning, permit, listening the teaching problem and together correction. Keywords :The Role of School Administrators; the Management of the Intensive Islamic Curriculum.